Effect of geometrical parameters on natural convection in a porous undulant-wall enclosure saturated by a nanofluid using Buongiorno's model - Hoghoughi, Gholamreza; Izadi, Mohsen; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal (Elsevier, 2018)
The paper refers to investigate the effect of geometrical parameters on natural convection of nanofluid over a cylindrical heater located inside of a porous undulant-wall cavity using local thermal non-equilibrium (LTNE) condition. Two phase-Buongiomo's model was applied to consider the thermal and flow indexes under geometrical variations. The validity of the numerical procedure was examined by contrasting the present and the previous works. The effect of governing parameters of the cavity, including horizontal and vertical displacement of cylindrical heat source (x and y respectively), the amplitude of the lateral wave walls (A) on streamlines, isotherms of two porous medium phases and also concentration of nanoparticles has been inquired. Overall, the results show that temperature distribution is different for the two phases in the porous medium, making it inevitable to utilize the non-equilibrium model for porous media. It is obvious that the flow is weakened as the heat source is elevated, while by the horizontal deviation of the flow toward a certain direction, it becomes stronger in the region opposite to the deviation and weakened at the deviated side. When the cylindrical heat source is located at the bottom of the cavity, the nanofluid becomes more homogeneous as a result of the agitation by strong vortices. As the corrugation amplitude of the lateral walls is increased, the nanofluid flow becomes stronger, leading to a more uniform distribution of nanoparticles around the cavity. At lower corrugation amplitudes, the average Nusselt number of the fluid is reduced as the heater is elevated. On the other hand, at higher amplitudes, the variations of the average Nusselt number of the fluid shows an increasing-decreasing trend as the cylinder is elevated. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Natural convection; Porous media; Local thermal non-equilibrium model; Buongiomo's model